Design and Analysis of a Wireless Temperature Monitoring System - Teoh, Wei Boon (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
Wireless temperature monitoring system for industrial application is widely used in nowadays. Radio Frequency (RF) is the frequency of radio waves and alternating currents which carry radio signals. The radio frequency range is from 3 kHz until 300 GHz. By using Amplitude-shift keying (ASK) to modulate the digital data as variations in the amplitude of carrier wave. The temperature sensor detects the surrounding temperature before transmitting it to a receiver. At the receiver, the temperature will be displayed on a Liquid crystal display (LCD) and laptop for easy monitoring. This paper highlights the robust verification method to ensure the accuracy of the sensing and transmitting the data. The result shows that the device can accurate by monitor and sensing the data with 99.9% accuracy.